Computational power of probabilistic simple one-sided sticker languages / Mathuri Selvarajoo ...[et al.] - Selvarajoo, Mathuri; Fong, Wan Heng; Sarmin, Nor Haniza; Turaev, Sherzod (Unit Penerbitan UiTM Kelantan, 2016)
A DNA model of computing using the recombinant behaviour of DNA molecules known as sticker system was introduced by Kari in 1994. Sticker system isan abstract computational model which uses the Watson-Crick complementarity principle of DNA molecules. It starts from incomplete double-stranded sequences and using sticking operations iteratively which bring about complete double-stranded sequences.Sticker system and its variants including simple one-sided sticker system with finite sets of axioms and sticker rules, generate only regular languages. Therefore, different types of restrictions have been introduced in order to increase the computational power of the languages generated by sticker systems. In recent times, sticker system with probability as restriction, known as probabilistic sticker system is introduced. In this system, probabilities are initially associated with the axioms, and the probability of newly generated string is computed by multiplying the probabilities of all occurrences of the initial strings used in the computation of the new string. In this paper, the computational power of probabilistic simple one-sided sticker systems is investigated. We prove that the probability restriction on simple one-sided sticker system can increase the computational power of the languages generated